2020
DOI: 10.46245/ijorer.v1i2.32
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor Skills of Pre-service Teachers of Natural Science on Melde’s Experiment in Guided Inquiry Learning

Abstract: This research aimed to describe the psychomotor skills of pre-service teachers of natural science on Melde’s Experiment through guided inquiry learning. Psychomotor skills were assessed by observation during students conduct the Melde’ s experiment. This research method used was descriptive quantitative in which the authors described the research variables from the collected data. The study was conducted on a pre-service natural science teacher who learns the Optic and Geometry Course. The data analysis uses d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…According to Payu (2023) and Sartika & Shofiyah (2020); the assessment of the psychomotor domain can be assessed on learning outcomes in the form of performances or activities during the learning process. From meeting I to IV there was an increase in students' skills which showed that the assessment carried out instilled changes in skills that were better for students.…”
Section: Psychomotor Competency Learning Resultsmentioning
confidence: 99%
“…According to Payu (2023) and Sartika & Shofiyah (2020); the assessment of the psychomotor domain can be assessed on learning outcomes in the form of performances or activities during the learning process. From meeting I to IV there was an increase in students' skills which showed that the assessment carried out instilled changes in skills that were better for students.…”
Section: Psychomotor Competency Learning Resultsmentioning
confidence: 99%
“…Science Learning Domain (Mork et al, 2021); (de Jong, 2019); (Papaevripidou & Zacharia, 2015); (Simorangkir & Rohaeti, 2019); (Wu et al, 2022); Domain 1 (Wilujeng et al, 2019); (Matteson, 2022); (Sartika & Shofiyah, 2020); (Wirzal et al, 2022) Domain 2 (Bustamante et al, 2018); (Sand et al, 2022); (Kelley & Knowles, 2016); (Ruben et al, 2020) Domain 3 (Indana et al, 2018); (Badrun et al, 2021) Domain 4…”
Section: Sourcesmentioning
confidence: 99%
“…Science is a science that focuses on the ability of students to be active in the learning process of the exploration process. In particular, current education seeks to help students learn to organize and construct opinions, formulate problems, develop hypotheses, and find evidence for themselves [3] and physics is a field of science that produces scientific components in the form of patterns of thinking, behavior and is carried out through scientific steps such as observation, problem formulation, hypothesis formulation, hypothesis testing, experimentation, making conclusions, to the discovery of a theory and concept through learning [4].…”
Section: Introductionmentioning
confidence: 99%